KELIMPAHAN MAKRO DEBRIS DI EKOSISTEM MANGROVE MUARA TUKAD MATI, BALI - Julihartadi, I Gede Dwian; Arthana, I Wayan; Ernawati, Ni Made (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2024)
Macro debris refers to waste materials ranging in size from 2.5 cm to 1 m, commonly found both on the water's surface and on the seabed. The accumulation of such large debris in coastal and marine environments can lead to various consequences, including disturbances to ecosystem stability and threats to the survival of organisms. Additionally, it diminishes the aesthetic quality of the environment. Among the ecosystems most susceptible to becoming repositories for this waste is the mangrove ecosystem. This study aims to quantify the amount, types, and abundance of macro debris scattered in the Tukad Mati Estuary Mangrove Area, Badung Regency, Bali. The research methodology involved several steps, starting with the selection of research stations. Transects measuring 5 x 5 meters were established. Within these designated areas, samples of macro debris were collected and categorized according to their composition, including materials such as plastic, fabric, glass, metal, and rubber. The results revealed that the total mass of macro debris collected in the Tukad Mati Estuary area amounted to 42,630 grams. The types of macro debris found in the Tukad Mati Estuary mangrove ecosystem consist of plastic, fabric, glass, metal, and rubber. Based on their quantity, the composition of macro debris is dominated by plastic at 87.02%, followed by fabric at 4.24%, rubber at 4.17%, glass at 2.67%, and metal being the least at 1.89%. Based on their weight, the composition of macro debris is highest for plastic at 32.33%, followed by rubber at 27.29%, fabric at 20.23%, glass at 14.36%, and metal being the lowest at 5.78%. The abundance of macro debris in the Tukad Mati Estuary mangrove ecosystem ranges from 0.85 items/m² to 10.68 items/m². Keywords: Marine Debris; Pollution; Tukad Mati Estuary; Mangrove